The Identity Constitution of the Craft Beer Consumer in the City of Fortaleza (Brazil) - João Gonçalves Menezes; Minelle E. Silva; José Sarto Freire Castelo (BBR: Brazilian Business Review)
With the transformation of the market into a provider of relevant symbolic resources, individuals like to demonstrate consumer goods that reflect their values and shared lifestyles. Thus, the aim of this study is to define identity profiles of craft beer enthusiasts based on their consumption practices. Using exploratory qualitative research, 55 consumers were interviewed and observations were made in the city of Fortaleza, Ceará, Brazil. The results present five consumer identity profiles in the culture of the craft beer consumer: Beginner, Adventurer, Beer Evangelist, Expert, and Beer Snob. The research enriches the studies inherent in consumer culture by presenting identity profiles based on consumption habits, and what is more, the research also makes a contribution by presenting the segmentation methodology in which the suggested identities can serve as a mechanism for industry organizations in the search for relationship strategies with the target audience.